Knowledge and Practice of Nurses and Midwives Regarding Immediate Care after Birth at Two Tertiary Centers in the Kurdistan Region - Nergz Bayiz Abdulrahman; Sazan Bahram Ahmed; Nazeera Tahseen Kareem; Suham Mirhamad Abdullah (Hawler Medical University, 2024)
Background and objectives: The first two hours following birth are considered the immediate postpartum period, which starts as soon as the placenta is delivered. During the first few days after giving birth, the mother and child should be seen as a unit, supported by their family and/or friends. The first two hours following the baby's birth correspond to the fourth stage of labor. Irregularly, deadlines are separated into three categories: urgent (within 24 hours), early (7 days), and late (6 weeks). The purpose of this study is to ascertain the nurses' and midwives' practices and knowledge of immediate postpartum care and its associated factor between socio-demographical characteristics of nurses and midwives' knowledge and our practice regarding immediate care after birth. Methods: A descriptive study was conducted in the Kurdistan region. The study was conducted at two hospitals, Maternity Teaching Hospital and Soran Maternity Hospital. The hospitals had several departments, such as the Neonatal Intensive Care Unit, Delivery Unit, Postpartum Unit, and Postoperative Unit. A purposive non-probability sample of fifty nurses and midwives from the delivery and postpartum unit was used. Version 23 of the Statistical Package for the Social Sciences was used to analyze the data. Results: More than half (51.9%) of the study samples' level of education was institute nursing, while MSc holders made up the highest percentage (1.9%). Most of the samples (71.2%) had trained less than 5 years. More than one-third (36.5%) of nurses-midwives have 15 years of experience. Almost all of the samples (94.2%) had high knowledge about immediate care after birth, and the highest percentage (71.2%) of samples had a good practice in caring for babies after birth. Conclusion: Midwives have a high level of practice in drying and wrapping babies immediately after birth, it can be concluded that most of the midwfe-nurses who participated in the study....